Study of changes in levels of salivary estriol and progesterone in preterm labor in comparison to normal pregnancy - Yadav, Richa; Singh, Urmila (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: This prospective research was designed to evaluate changes in levels of salivary Estriol and Progesterone in preterm labor in comparison to normal pregnancy. Spontaneous onset of labor at term is produced by definite increase in estriol and fall in progesterone. This rise in free estrogen should precede the onset of labor according with the known effect of estrogen and progesterone on myometrial activity. Concentration of steroid in saliva reflect unbound unconjugated and biologically active fraction. Methods: The present study was carried for duration of one year enrolling 115 antenatal women between 28 and < 37 weeks of gestation with or without labour pains attending the antenatal clinic in KGMU, Lucknow and those admitted in Queen Mary’s Hospital Lucknow. 5 ml of saliva was collected in cryovials from each patient to estimate estriol and progesterone. The estimation of saliva progesterone and estriol was done by immunoenzymatic colorimetric method of the supernatant of sample. Results: In our study mean value of saliva progesterone levels of pregnant women with preterm delivery (study group IIA) was lower than the control group (Group l) but the difference was not significant (3814.46±751.14 pg/ml versus 3945.16±577.11 pg/ml, p = 0.351). Mean value of estriol study group who delivered preterm (3512.85±586.16 pg/ml) was higher as compared to the mean value of control group (2691.72±681.08 pg/ml) and difference was significant (p value < 0.001). Conclusions: Thus, there is significant rise in level of saliva estriol, it can be used as a predictor for detecting symptomatic and asymptomatic women at risk for preterm birth.